7y+5+(3y)=

Simple and best practice solution for 7y+5+(3y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y+5+(3y)= equation:


Simplifying
7y + 5 + (3y) = 0

Reorder the terms:
5 + 7y + (3y) = 0

Combine like terms: 7y + (3y) = 10y
5 + 10y = 0

Solving
5 + 10y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 10y = 0 + -5

Combine like terms: 5 + -5 = 0
0 + 10y = 0 + -5
10y = 0 + -5

Combine like terms: 0 + -5 = -5
10y = -5

Divide each side by '10'.
y = -0.5

Simplifying
y = -0.5

See similar equations:

| 5a-4(a-8)=3+2a | | t*g^2*x-(1)=0 | | -6.5x^2+1.6+24=0 | | (-7)-(-2)= | | 4l^4m^5n^6/5mn= | | y=22-9 | | 4g^2= | | 13-2j=-29 | | 8×2/3 | | 4p+34.8=68 | | 9n^6-16p^2= | | 33-y=2 | | 6(1k-7)-2=5 | | 7+(-7)= | | 4x^2+7=4x+6 | | y=-16x^2+60x+6 | | y+3=0fory | | 5x^2-10=x^2+71 | | 3t+5+3t-5t=6+5 | | 16t^2+40tx+25x^2= | | x/3=-2-(-6) | | 6(-5/7) | | 20m-35= | | (4x-20)=(2x+10) | | x-4(99-11x)-1.584=0 | | -3(3y+1)-13=-6(y+5)+3y | | (-6)-1= | | (2x^2)/(.5-x^2) | | 3x-2x-9=2 | | a^2+25+10a=0 | | (-1)+2= | | 3x-2x-9=3 |

Equations solver categories